Perceived Usage of E-Wallet among the Y Generation in Surabaya based on Technology Acceptance Model - Pertiwi, Dewi; Suprapto, Widjojo; Pratama, Eric (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2020)
Although the government of Indonesia is building the cashless society, the number of e-wallet users are increasing slowly. E-wallet is becoming a common instrument of payments from the paper-based instruments to server-based electronic money. The aim of this research is to investigate the perceived usage of the Y Generations on e-wallet based on Technological Acceptance Model (TAM) which is a powerful model to describe single approval to the usage of a new information technology system. As a quantitative research, the data analysis is using the Partial Least Square (PLS) with the SmartPLS 3.0 software. The results show that perceived usefulness and perceived ease of use brings impacts positive significant impacts to behavioural intention to use, then, the behavioural intention to use affect a positive significant impact to perceived usage. However, a direct effect from perceived usefulness to perceived usage shows a negative and no significant impact, meanwhile an unintended effect from perceived usefulness to perceived usage through behavioural intention to use show a positive significant impact. Finally, a direct effect from perceived ease of use to perceived usage shows a lower t-statistic value than an indirect effect from perceived ease of use to perceived usage through behavioural intention